Cupressus Torulossa Progeny Test: Variability and Heritability Estimates - Gangoo, S. A.; Masoodi, N. A.; Murtaza, Shah (Indian Forester, 2014)
The narrow sense heritability for various progeny trials of Cupressus torulossawas assessed. There was obviously much variation in the degree to which traits are under additive genetic control. Height is strongly controlled genetically followed by base branch angle and then by collar diameter. The coefficient of variation (C.V.) being a unit less measurement is a good basis for comparing the extent of variation between different characters with different scales. Here GCV (genotypic coefficient of variation) and PCV (phenotypic coefficient of variation) is highest for height. Heritability is of key importance in estimating gains that can be obtained from selection programme.